2013
DOI: 10.3389/fphar.2013.00125
|View full text |Cite
|
Sign up to set email alerts
|

Beyond osteogenesis: an in vitro comparison of the potentials of six bone morphogenetic proteins

Abstract: Bone morphogenetic proteins (BMPs) other than the clinically available BMP-2 and BMP-7 may be useful for improving fracture healing through both increasing osteogenesis and creating a favorable healing environment by altering cytokine release by endogenous cells. Given the spectrum of potential applications for BMPs, the objective of this study was to evaluate various BMPs under a variety of conditions to provide further insight into their therapeutic capabilities. The alkaline phosphatase (ALP) activity of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“… demonstrated that exogenous BMP‐9 up‐regulated expression of SDF‐1‐alpha by human endothelial cells and Rivera et al . reported that exogenous BMPs, including BMP‐4, ‐6, and ‐9, increased SDF‐1 production in human bone marrow stromal cells. However, Liu et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… demonstrated that exogenous BMP‐9 up‐regulated expression of SDF‐1‐alpha by human endothelial cells and Rivera et al . reported that exogenous BMPs, including BMP‐4, ‐6, and ‐9, increased SDF‐1 production in human bone marrow stromal cells. However, Liu et al .…”
Section: Discussionmentioning
confidence: 97%
“…In our study, rhBMP-9 modestly enhanced the level of SDF1a mRNA and the levels of SDF-1 protein in PDLFs cultured in the osteogenic medium, and the rhBMP-9-stimulated SDF-1 production was suppressed by LY294002. YOUNG et al (23) demonstrated that exogenous BMP-9 up-regulated expression of SDF-1-alpha by human endothelial cells and RIVERA et al (10) reported that exogenous BMPs, including BMP-4, -6, and -9, increased SDF-1 production in human bone marrow stromal cells. However, LIU et al (24) reported a reduction of SDF1 mRNA in C3H10T1/2 cells following delivery of BMP-9 by an adenoviral vector.…”
Section: Discussionmentioning
confidence: 99%
“…These results in combination with the micro‐CT and H&E histological staining conclude that a large amount of new bones has been formed around the down edge of the collagen scaffold after 30 days of hMSCs' transplantation (Figure A,B), evidencing that the transplanted hMSCs can facilitate bone formation around their habitat via osteogenic differentiation. The osteogenic differentiation of transplanted hMSCs can also be distinctly improved by BMP‐2 treatment through BMP signaling pathway . As shown in Figure B, the expression of the transcriptional factors and transcriptional co‐activators (Runx2 and Osterix) was significantly upregulated after BMP‐2 treatment.…”
Section: Resultsmentioning
confidence: 92%
“…As shown in Figure C, the expression of stromal cell–derived factor‐1α (SDF‐1α), basic fibroblast growth factor (FGF), and BMP‐2 genes was highly active in hMSCs. It is known that the SDF‐1α is a vital chemokine for regulating stem cell migration and homing, the FGF is a key factor involved in cell proliferation, and the BMP‐2 is a crucial factor for osteogenic differentiation of cells . Thus, these cytokines excreted by the transplanted hMSCs helped to recruit endogenous osteoblasts at the bone defect site and promoted bone regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there are several other murine cell lines that, under appropriate stimuli, can be induced to differentiate into osteoblasts in vitro. For instance, the mouse myoblast cells C2C12 differentiate along the osteogenic lineage in presence of BMPs and the embryo-derived fibroblasts NIH3T3 adopt an osteoblast-like phenotype when treated with 1α,25-dihydroxyvitamin D(3) and dexamethasone [52][53][54].…”
Section: Non-transformed Cell Linesmentioning
confidence: 99%